Oneiric Plots as a Reflection of the Real and Unreal World of Characters in the A.P. Chekhov’s Prose (Proceedings of Southern Federal University. Philology, 2018)
Li Huo (Rostov-on-Don, Russian Federation)Dreams are a part of a person’s life, therefore people may recognize dreams reflection in art works. Dreams as phenomena of a certain physiological state can be filled with plots that are a representation of both a real-life situation and a situation that does not exist in reality. Unreal situations in the dreams of the characters in the prose of A.P. Chekhov are connected with reality. The idea of the character world is formed in works that have oneiric plots, from a combination of real events with events that are unreal. They help to reveal the nature of the character, his attitude to different life situations in real life.Key words: dream, character world, storylines, reality, unreality.DOI 10.23683/1995-0640-2018-3-132-137